How women's responsibilities during war impacted their drive for social, economic, and political change - Buxrude, Alison (My University, 2012)
Wartime experiences for women, while husbands and brothers were gone at war, led to the idea that women were capable of social, economic and political change. The following presentation will outline these changes during the American Revolution, the Civil War, and two World Wars, and the Cold War Era and include examples of recipes these women used on the home-front to help visualize these changes in their lives.
Color poster with text and images
Keywords: Posters; Women--United States--History; Women--United States--Social conditions; Women and war--United States--History; Women--Political activity--United States--History